2011
DOI: 10.1016/j.ultrasmedbio.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Long-Term Venous Occlusion Using Pulsed High-Intensity Focused Ultrasound Combined with a Pro-Inflammatory Agent

Abstract: Esophageal and gastric varices are associated with significant morbidity and mortality for cirrhotic patients. The current modalities available for treating bleeding esophageal and gastric varices, namely endoscopic band ligation and sclerotherapy, require frequent sessions to obtain effective thrombosis and are associated with significant adverse effects. A more effective therapy that results in long-term vascular occlusion has the potential to improve patient outcomes. In this study, we investigated a new po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have demonstrated HIFU occlusion in blood vessels of small diameters only (range 0.5-1.5 mm) (Delon-Martin et al 1995, Hynynen et al 1996a, 1996b, Rivens et al 1999, Denbow et al 2000, Ishikawa et al 2003, Hwang et al 2005, Ichihara et al 2007, Ichizuka et al 2007, Hwang et al 2010, Zhang et al 2010, Fujiwara et al 2011, Zhou et al 2011, Shaw et al 2014. The occlusion of large vessels (⩾2 mm) has not been reported to the best of our knowledge.…”
Section: Noninvasive Vascular Occlusion With Hifu For Venous Insuffic...mentioning
confidence: 80%
See 2 more Smart Citations
“…Previous studies have demonstrated HIFU occlusion in blood vessels of small diameters only (range 0.5-1.5 mm) (Delon-Martin et al 1995, Hynynen et al 1996a, 1996b, Rivens et al 1999, Denbow et al 2000, Ishikawa et al 2003, Hwang et al 2005, Ichihara et al 2007, Ichizuka et al 2007, Hwang et al 2010, Zhang et al 2010, Fujiwara et al 2011, Zhou et al 2011, Shaw et al 2014. The occlusion of large vessels (⩾2 mm) has not been reported to the best of our knowledge.…”
Section: Noninvasive Vascular Occlusion With Hifu For Venous Insuffic...mentioning
confidence: 80%
“…Hwang et al (2010) used pulsed HIFU exposures with a low duty cycle in synergy with ultrasound contrast agent. The treatment was effective but could not maintain rabbit auricular vein occlusion over 14 d. With similar pulsing regime (9 MPa peak rarefaction pressure, 1 Hz pulse repetition frequency), Zhou et al (2011) demonstrated a sustainable occlusion with mechanical effects of HIFU but only by injecting proinflammatory agents corresponding to the detergents found in sclerosing agents (Loffroy et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to endovenous thermal therapies, Highintensity focused ultrasound (HIFU) can heat tissues noninvasively [16]. The use of HIFU as a noninvasive alternative to endovenous treatments of varicose veins has already been investigated in a number of preclinical studies [17][18][19][20][21][22] and the ability to occlude small veins in vivo noninvasively with thermal HIFU has been demonstrated [18,22]. However, the efficacy and safety of the ablative procedures were demonstrated in the short term only, at most two weeks after treatments [22].…”
Section: Introductionmentioning
confidence: 99%